The development of drinking water supply system performance index using chemometric technique in Selangor, Malaysia - Heirlyn@Musyra Zolkipli
Water pollution quite happened in every single point of water source especially on river. Almost 40% of river was declared as a dead river or in class IV in Selangor, Federal Territory of Kuala Lumpur and Putrajaya area. Therefore, Malaysia Ministry of Health (MOH) was established Drinking Water Quality Surveillance Programme (DWQSP) to monitor the quality of drinking water supply provided to consum rs by ensuring that complies with the drinking water quality standards (DWQS) thereby reducing the incidence of water-borne diseases or intoxication associated with poor quality public water supplies. The main objective in this research is to develop the drinking water supply system performance index using chemometric technique, to identify the spatial variation of the drinking water quality parameters based on different category stations and to analyse the most possible sources affecting drinking water quality parameters on treated water. Five years secondary data starting 2012 until 2016 with four group drinking water quality parameters (physical biological- PBP, in-organic- lOP, heavy metal and organic- HMOP, pesticide parameter- PP) was used in this research. The raw data come from MMOH which is the sampling task located at all the public water supply systems in Selangor, Federal Territory of Kuala Lumpur and Putrajaya Distinct. Point of studied are Raw (R), Treatment Plant Outlet station (TPO), Service Reservoir Outlet (SRO) and Auxiliary (A). R station called treated water then TPO, SRO and A stations called treated water. Discriminant analysis (DA) using to determine the spatial variation of the drinking water quality parameters. Thus, Principle Component Analysis (PCA) is a statistical analysis used to identify the most possible sources of pollutant influence the drinking water quality parameters and to develop the drinking water supply system performance index. Consequently, confusion matrix in stepwise/ backward forward standard mode for four sampling station defined that the drinking water pollutants were excellent in result of discrimination 94.91 % and lout of 38 parameters showed no significant parameter (p>0.05). Thus, PCA analysis successful resulted the possible Sources of pollutant and the development of DWSSI with five categories of its scale performance including excellent, good, moderate polluted and very polluted. The excellent performance 59.41 % followed by good performance value 38.23%, moderate, polluted and very polluted performance are 2.23, 0.12% and 0.01 %. Using this scientific approach will define the index of drinking water pply system and reducing the drinking water quality parameters in the futu sampling task. This finding will simplify MMOH and will reducing of parameter, cost and time during sampling task. Further, the Chemometric techniques in the large da aset of the NDWQS are considerably the most reliable, effective and low cost to manage the quality of drinking water for our country.